Digitising psychiatry? Sociotechnical expectations, performative nominalism and biomedical virtue in (digital) psychiatric praxis. (2nd September 2018) - Pickersgill, Martyn
Abstract: Digital artefacts and infrastructures have been presented as ever more urgent and necessary for mental health research and practice. Telepsychiatry, mHealth, and now digital psychiatry have been promoted in this regard, among other endeavours. Smartphone apps have formed a particular focus of promissory statements regarding the improvement of epistemic and clinical work in psychiatry. This article contextualises and historicises some of these developments. In doing so, I show how purportedly novel fields have been constituted in part through practices of 'performative nominalism' (whereby articulations of a neologism in relation to established and recent developments participate in producing the referent of the new term). Central to this has been implicit and explicit extolment of what I term biomedical virtues in public‐facing and professionally orientated discourse. I document how emphases on various virtues have shifted with the attention of psychiatry to different digital modalities, culminating with knowledge‐production in mental health as one significant focus.